Upaya Peningkatan Kualitas Guru Dalam Mencegah Perundungan Melalui Platform Merdeka Mengajar Jenjang Sma Di Kota Pontianak - Fitri Pratiwi; Sari'ani Sari'ani; Mindariati Mindariati; Warneri Warneri; Aunurrahman Aunurrahman (Journal on Education, 2024)
The aim of this research is to provide teachers with facilities through the Merdeka Mengajar Platform (PMM) in handling and identifying cases of bullying and how to prevent bullying in the educational unit environment. The type of research is qualitative research, namely by means of literature study, the researcher examines the social phenomena that occur. Researchers use library research with the techniques used in research are observation and interviews. One of the materials in the independent training at PMM is Safe School Climate: Preventing Bullying. Implementation of bullying prevention in Pontianak State High School by training teachers, and approaching students, because students are the source of bullying at school. Training focuses on increasing belief in God Almighty and improving norms and laws, training aims to improve students' character.